Static analysis of laminated and sandwich composite plates based on simple refined higher-order displacement theory - Tu, Tran Minh (Vietnam Journal of Mechanics, 2010)
A simple refined higher-order displacement theory is used for the static analysis of laminated and sandwich plates. Both analytical and finite element solutions are developed. Numerical examples of laminated and sandwich plates are given for different thickness ratios, length-to-thickness ratios to illustrate the accuracy of the present formulation by comparing the present results with results already available in the literature.